Development and preliminary validation of the evaluation scale for nurses’ core emergency response abilities in sudden major infectious disease outbreaks - Yuxin Zhu; Mengjuan Jing; Xiulu Xu; Jiamei Jing; Hanghang Jin; Jiaxin Li; Liming Li (BMC Nursing)
Abstract Background In recent years, the escalating frequency and intensity of infectious disease outbreaks have underscored the profound severity and global ramifications of public health challenges confronting healthcare systems. As frontline responders during emerging infectious disease crises, nurses’ core emergency response competencies critically influence the timeliness and efficacy of outbreak prevention and control measures. Currently, standardized assessment instruments for evaluating nurses’ core emergency response capabilities during major infectious disease outbreaks remain underdeveloped. Aims This study aimed to construct and psychometrically validate a Core Emergency Response Competency Evaluation Scale for nurses during major infectious disease outbreaks. Methods A convenience sample of nurses was recruited from eight tertiary hospitals in Henan Province, China. The three-phase study comprised: (1) item generation (Delphi survey and pilot testing), (2) scale development (item analysis and exploratory factor analysis), and (3) scale validation (reliability and validity assessments). Results The finalized 45-item scale encompasses eight dimensions: Fundamental Nursing Knowledge, Legal Policy & Ethical Practice, Core Nursing Skills, Disease Assessment & Monitoring, Emergency Response Coordination, Infection Prevention & Control, Nurse Personal Attributes, and Rehabilitation & Recovery. Exploratory factor analysis demonstrated an 83.353% cumulative variance contribution for the eight-factor model. Confirmatory factor analysis indicated excellent model fit (χ²/df = 1.943, RMR = 0.020, RMSEA = 0.050, IFI = 0.951, TLI = 0.947, CFI = 0.951, PNFI = 0.835). The scale exhibited strong reliability (Cronbach’s α = 0.987, split-half = 0.956, test-retest = 0.977) and validity (I-CVI = 0.875-1.00; S-CVI = 0.974). Convergent validity was supported by AVE values (0.611–0.778) and CR values (0.903–0.955). Conclusion The psychometrically robust Core Emergency Response Competency Evaluation Scale for Sudden Major Infectious Diseases demonstrates excellent reliability and validity, providing a scientifically validated tool for assessing nurses’ emergency preparedness in infectious disease crises.